Respons Imun Ayam Petelur Pascavaksinasi Newcastle Disease dan Egg Drop Syndrome - Gusti Ayu Kencana; I Nyoman Suartha; Daniel Raja Bonar Nainggolan; Agatha Seren Lumban Tobing (Jurnal Sain Veteriner, 2017)
Some viral diseases in poultry could lead to huge losses to the farmers. Newcastle Disease (ND) and Egg Drop Syndrome (EDS) are a group of infectious viral disease that can cause the decreasein egg production. Newcastle Disease is caused by Avian paramyxovirus type 1 (PMV-1) Paramyxoviridae family. The causative agent of EDS is Duck adenovirus-I Adenoviridae family. Both of these diseases affect the economic losses to the poultry. The main action to prevent hens from ND and EDS virus diseases is vaccination. The success ofvaccination can be tested by serology. ND and EDS virus characteristically agglutinate hen’s erythrocyte they have Hemagglutine protein on virus envelope so can be tested by hemagglutination. The study was conducted ona commercial poultry farm in order to determine the success of vaccination against ND and EDS. The hens were vaccinated by Newcastle Disease-Infectious Bronchitis- Egg Drop Syndrome (ND-IB-EDS) inactivated vaccines.Serological test was conducted in pre and post vaccination by using microtiter hemagglutination test. The antibody titre is expressed in units of HI log2. The results of the study, the mean antibody titer against ND pre vaccinationwas 4,53 ± 1,356 HI log2 and antibody titre in 2nd, 3rd and 4th week were 8,67 ± 0,617 HI log2, 7,73 ± 1,335 HI log2 and 5,20 ± 0,862 HI log2 post vaccination. Antibody titre against EDS pre vaccination was 0 ± 0,000 HI log2 and antibody titre post vaccination in 2nd, 3rd and 4th week were 7 ± 1,363 HI log2, 7,27 ± 1,438 HI log2 and 7,6 ± 1,056 HI log2. It showed that ND-IB-EDS inactivated vaccines is serological protective for ND and EDS titres.